The Lived Experiences of Psychological Well-Being among Generation Z Contract Teachers: A Phenomenological Study - Ardhinto Bagus Prakoso; Roro Setyawati (The Future of Education Journal, 2026)
The ability of understanding of mathematical concepts has a very important in required learning objectives of mathematics should be developed through a learning process. However,  mathematics learning happens in class IV SDN 06 Punggung Lading and SDN 12 Cubadak Mentawai is not optimally involving students in process to find the concept so the students ability of mathematical understanding is not developed. So the ability of students’ understanding of mathematical concepts is still low. Alternativers that could be used as a solution to overcome this problem was using model Cooperative Learning type TSTS. The research aim to know whether the students’ understanding concepts of mathematical using cooperative learning type TSTS is better than conventional learning. SDN 06 Punggung Lading was assigned as the experimental class taught using the model cooperative learning type TSTS, while SDN 12 Cubadak Mentawai served as the control class taught using conventional learning.This type of research is quasi-experimental with the design Static Group Design. Based on the data analyses result concluded that the students understanding concept of mathematical using Cooperative Learning type TSTS is better than conventional learning.